Spatial-temporal changes in pH, structure and rheology of the gastric chyme in pigs as influenced by egg white gel properties. (15th May 2019) - Nau, Françoise; Nyemb-Diop, Kéra; Lechevalier, Valérie; Floury, Juliane; Serrière, Chloé; Stroebinger, Natascha; Boucher, Thiébaud; Guérin-Dubiard, Catherine; Ferrua, Maria J.; Dupont, Didier; Rutherfurd, Shane M.
Highlights: Gastric emptying in pigs was slower with the smooth-rigid egg white gel. Gastric acidification started at the pylorus region in pigs fed with egg white gels. The change of gastric pH profile depended on the egg white gel characteristics. The smooth-rigid egg white gel resulted in the largest particles in gastric chyme. Distal and proximal chymes did not differ in dry matter, particle size and rheology. Abstract: The hypothesis is that the characteristics of ingested protein gels influences the subsequent in vivo gastric digestion process. Three egg white gels (EWGs) of identical composition but differing in structure and texture were prepared and fed to pigs. Sampling throughout a 6 h postprandial period, and at different locations in the stomach of the pigs, enabled a detailed spatial-temporal mapping of the pH, dry matter content, particle size and rheological properties. The results showed different gastric acidification kinetics implying an effect of the gel structure and/or texture. The most elastic and cohesive gel resulted in the highest median particle size and the most viscoelastic chyme. Distal and proximal regions of the stomach did not differ in terms of dry matter content, particle size distribution or rheological properties. These results demonstrate the consequences of protein food structure on gastric chyme properties, and thus suggest an effect on the digestion process.